Pertanggungjawaban Pidana Terhadap Korporasi di Indonesia - Rini Retnowinarni (Faculty of Law Hang Tuah University, 2019)
Criminal liability against corporations in Indonesia is still ambiguous, because the Criminal Code cannot capture corporations as legal subjects who can be convicted, because it still adheres to the principle of the subject of law is only natural man. Some laws and regulations outside the Criminal Code have begun to deviate from the general principle, by trying to put corporations as the subject of criminal law and the problem of criminal liability. In the ius constituendum perspective the subject of corporate crime and criminal liability has been formulated explicitly and in detail in the draft draft Criminal Code 2006, Article 44 to Article 50. Thus in principle the corporation has been accepted as a legal subject in criminal law, so that the corporation can be prosecuted and sentenced criminal. The acceptance of the principle which deviates from the principle of error is not contrary to the philosophy of the Pancasila. In other words, the deviation of the principle of error has juridical, sociological, and philosophical relevance.